Relações de Significação na Seção de Leitura de Exames de Proficiência em Língua Inglesa: universidade e internacionalização - Salles, Jaqueline Laís de (2020)
The process of internationalization of science in Higher Education Institutions (HEIs) provides effective collaboration in the development of new ideas, studies and technologies. In Brazil, this process gained strength, albeit belatedly, with the creation of the program Ciência sem Fronteiras, in 2011, and since then, HEIs have been working to advance in the international science field. In this context, it is a fact, according to a questionnaire made by CAPES (BRAZIL, 2017), that most foreign scholarship opportunities are distributed in English-speaking countries, and the first requisite for an exchange program is the presenation of a proficiency exam accepeted by the institution provider of the vacancy. Among the proficiency tests available in this context, the Test of English as a Foreign Language - Institutional Testing Program (TOEFL-ITP) and the B2 First of Cambridge are the exams with the highest acceptance rates. Thus, actions and tools are necessary to better prepare candidates in academic level for these exams. In this study, we show that studies on lexicology, more specifically, on word relationships, i.d., the relation which words stabilish among themselves and their meanings, contribute significantly to the preparation of students to the exams, especially with regard to reading strategies in these exams. Therefore, the theme of this research is the word relationships, more specifically homonymy, polysemy and parasynonymy, in the exercises of the reading section in official preparatory materials of the TOEFL ITP and B2 First exams between 2010 and 2019. Hence, we question: what are the word relationships present in the exercises of the reading sections of these tests? How often do these relationships appear? And, what is the relevance of working with meaningful relationships in the preparation for these exams? Aiming to make a survey of the types of word relationships which appear in the exercises of the reading sections of the preparatory material of the TOEFL ITP and B2: First international exams. As theoretical basis we will rely on Knight; De Wit (1997); Teichler (2004); Altbach (2007); Morosini (2011) and Moore (2019) to research about internationalization; and in Ulmann (1974), Pottier (1978); Helmslev (1985); Biderman (2001); Oliveira and Isquerdo (2001); Zavaglia (2003) and Barbosa (2009) for lexicology studies. This is a quanti-qualitative research, with a bibliographic and documentary nature. As a result, we present a series of data collection which aim to contribute to the preparation to the exams, for exemplo, the types of texts in the reading section; the study fields highly present and the types of exercises which appear as a pattern. Moreover, we prove that the study in homonymy, polysemy and parasynonymy are of great importance to the candidates in the preparation fase, reaching 1/3 of the reading section grade in one of the analyzed exams.